A pocket guide to understanding Alzheimer's disease and other dementias - Warner, James (James Peregrine William), 1962-; Graham, Nori (Jessica Kingsley Publishers, 2018)
Includes key information on different types of dementia, this concise pocket-sized book lets you know about the symptoms to look out for, guides you through the diagnosis process and explains the treatments available. Like having a GP in your pocket, it also offers expert advice for living day-to-day with dementia, and where to go to get support.